Economic feasibility for the cost of land use provided for construction: a case study of the Stavropolsky municipal district of Samara region. Issue 1 (March 2020) - Bocharov, A Yu; Gordeeva, T E; Spirina, E S
Abstract: The value of a land plot or property rights to it is an important link in the investment and construction design. This paper considers a transparent, comprehensible and justified mechanism for the development of cost parameters using a case study of land plots provided for construction located on the territory of the Stavropolsky municipal district of Samara Region. The obtained cost indicators of the land use provided for construction are determined based on the analysis and examination of not only real lease agreements but also using alternative calculations. While calculating the indicators, the authors applied the principles taken from the Decree of the Government of the Russian Federation of July 16, 2009 No. 582 as well as the analysis of real land lease contracts for construction and calculations based on current standards and the development of construction costs based on aggregated indicators.